The effects of mobile devices and wireless technology on e-learning - Sasidhar, B.; Burra, Venkata Durga Kumar * (Sunway University College, 2005)
This paper examines factors influencing e-learning. A survey-based methodology was used to obtain data from respondents, namely, students in three higher educational institutions. The dependent variable in this study was effectiveness of e-learning and the independent variables were the impact of wireless technology and mobile devices, and demographic factors such as gender, age and course of study. Multiple regression analysis, correlation analysis, and chi-square test for independence were employed to analyze the data. Wireless technology and mobile devices were found to be the most important determinants of effectiveness of e-learning. There was no significant effect of course of study, age and gender on effectiveness of e-learning.